(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2014)
This paper presents the methods and techniques used to create a multimodal interaction robot. This multimodal interaction allow to the robot interact with multi – users at the same time. In order to facilitate common tasks in nondeterministic environments, where several people needs to interact, such as a classroom. It has created a socially assistive robot endowed with anthropomorphic and cognitive features that gives you a sense of realism to the user, namely the user thinks for a considerable period of time that really is interacting with a living being.